2001
DOI: 10.1080/08897070109511442
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in Egyptian Substance Abusers

Abstract: Alexithymia is thought of as a trait that predisposes to drug abuse. Moreover, it is suggested to be related to type of the substance abused, with the worst-case scenario including a worse prognosis as well as tendency to relapse or even not to seek treatment at all. To address this important subject in Egyptian patients, a sample of 200 Egyptian substance abusers was randomly selected from inpatients in the Institute of Psychiatry, Ain Shams University, Egypt. The study also included 200 group-matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…These results agree with the findings of previous studies (Rasheed, 2001;Pinard et al, 1996;Thorberg et al, 2009;Uzun, 2003;Cleland et al, 2005;Besharat, Nourbakhsh , Rostami, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results agree with the findings of previous studies (Rasheed, 2001;Pinard et al, 1996;Thorberg et al, 2009;Uzun, 2003;Cleland et al, 2005;Besharat, Nourbakhsh , Rostami, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…A study on the addicted men in Egypt showed that people who took several substances were more prone to alexithymia than people who took one drug (Rasheed, 2001). Also the results of several studies have confirmed the positive relationship between alexithymia and severity of alcohol use disorder (Cecero and Holmstrom, 1997;Haviland et al, 1988).…”
Section: Introductionsupporting
confidence: 49%
“…A number of studies suggest that these two mechanisms are associated with PTSD (APA, 1994; Feeny, Zoellner, Fitzgibbons & Foa, 2000; Hyer, Woods, Summers, Boudewyns, & Harrison, 1990; Monson, Price, Rodriques, Ripley, & Warner, 2004; Tull, Barrett, McMillan, and Roemer, 2007) and SUDs (El Rasheed, 2001; Fox, Axelrod, Paliwal, Sleeper, & Sinha, 2007; Loas, Fremaux, Otmani, Lecercle, & Delahousse, 1997). For example, in a sample of substance users, Handelsman and colleagues (2000) found a relationship between difficulty recognizing and naming emotions and PTSD symptoms (see Zlotnick, Mattia, & Zimmerman, 2001 for similar results).…”
Section: Introductionmentioning
confidence: 99%
“…As one ex-user protests, it "wasn't healthy to mute the world the way benzos do it" (Drugs-forum, 2014). Known as alexithymia, the inability to process or express emotion is a phenomenon reported in drug users and ex-users (El Rasheed, 2001;Lindsay & Ciarrochi, 2009). Lindsay and Ciarrochi found a lack of correspondence between perceived and clinical alexithymia in their study of newly abstinent substance users.…”
Section: Biographical Disruptionmentioning
confidence: 99%